Gadolinium leakage in ocular structures: a novel MRI finding in transient global amnesia - Förster, Alex; Wenz, Holger; Böhme, Johannes; Groden, Christoph (Journal of the neurological sciences, 2019)
Background and purpose - We investigated the frequency and pattern of blood-brain barrier as well as blood-retina barrier impairment in transient global amnesia (TGA) as demonstrated by hyperintense acute reperfusion marker (HARM) and gadolinium leakage in ocular structures (GLOS) respectively on fluid attenuated inversion recovery images (FLAIR). - Methods - Patients with TGA who underwent repeated MRI after intravenous contrast agent administration were identified and the presence of GLOS in the anterior chamber and vitreous body and HARM noted on FLAIR. - Results - Overall 10 patients (IQR 64.25-71.75years; 4 (40%) patients were male) were included. On contrast-enhanced FLAIR, GLOS was observed in 3 (30%) patients; in all of these in the anterior chamber and vitreous body as well as bilateral and symmetrical. HARM was observed in none of the patients. Frequency of hippocampal DWI lesions, as well as extent of age related white matter lesions did not differ significantly between patients with and without GLOS. - Conclusions - In contrast to HARM, GLOS is a relatively common finding in TGA patients. As GLOS is thought to share its pathophysiology at least to some extent with HARM and is associated with HARM in ischemic stroke, it might be used as surrogate marker for blood-brain barrier impairment in TGA.
Gesehen am 19.11.2019